Modelling Enforcement and Compliance in Fisheries: A Survey - Coelho, M. P.; Filipe, J. A.; Ferreira, M. A. M. (International Journal of Latest Trends in Finance and Economics Sciences, 2013)
Monitoring and enforcement considerations have been largely ignored in the study of fishery management. This paper discusses this issue with a formal model to show the impacts of costly, imperfect enforcement of law on the behaviour of fishing firms and fisheries management. Theoretical analysis combines a standard bio-economic model of fisheries(Gordon/Schaefer) with Becker’s theory of Crime and Punishment.